Increased Central and Peripheral Thyroid Resistance Indices During the First Half of Gestation Were Associated With Lowered Risk of Gestational Diabetes—Analyses Based on Huizhou Birth Cohort in South China - Liu, Zhao-min; Li, Guoyi; Wu, Yi; Zhang, Di; Zhang, Sujuan; Hao, Yuan-Tao; Chen, Weiqing; Huang, Qi; Li, Shuyi; Xie, Yaojie; Ye, Mingtong; He, Chun; et al. (Frontiers in Endocrinology, 2022)
Objectives The study aimed to explore the relationship of thyroid function and resistance indices with subsequent risk of gestational diabetes (GDM). Design This was a longitudinal study embedded in the Huizhou Birth Cohort. Methods A total of 2,927 women of singleton pregnancy were recruited from January to October of 2019. Thyroid central resistance indices were evaluated by Thyroid Feedback Quartile-Based index (TFQI), Thyrotrophy T4 Resistance Index (TT4RI), and TSH Index (TSHI) based on plasma-free thyroxine (FT4) and thyroid-stimulating hormone (TSH) levels during the first half of pregnancy. Thyroid peripheral sensitivity was assessed by free triiodothyronine (FT3) to FT4 ratio (FT3/FT4), a proxy of deiodinase activity. GDM was diagnosed between 24 and 28 weeks of gestation by a standardized 75 g oral glucose tolerance test. Multivariable linear and logistic regression was applied to examine the associations of thyroid markers with GDM risk. Results FT3 and FT3/FT4 were positively associated with both fasting and post-load glucose levels, while TSH, TSHI, TT4RI, and TFQI were negatively associated with 1 and 2 h post-load glucose levels. Compared with the lowest quartile, GDM risk in the highest quartile increased by 44% [odds ratio (OR) = 1.44; 95%CI, 1.08–1.92; ptrend = 0.027] for FT3 and 81% (OR = 1.81; 95%CI, 1.33–2.46; ptrend < 0.001) for FT3/FT4, while it lowered by 37% (OR = 0.63; 95%CI, 0.47–0.86; ptrend = 0.002] for TSHI, 28% for TT4RI (OR = 0.72; 95%CI, 0.54–0.97; ptrend = 0.06), and 37% for TFQI (OR = 0.63; 95%CI, 0.46–0.85; ptrend < 0.001). Conclusions This longitudinal study indicated that higher FT3 and FT3/FT4 and lower central thyroid resistance indices were associated with increased risk of GDM.